'Two faces, each of a confused countenance': Coleridge, De Quincey, and Contests of Authority. Issue 3 (October 2021) - Morrison, Robert
Abstract : Thomas De Quincey exploits his rivalry with Samuel Taylor Coleridge to structure many of the key features of his most famous work, 'Confessions of an English Opium-Eater' (1821). De Quincey's idolization of Coleridge began early and survived the anger and disappointment he felt after the collapse of their friendship and his discovery of Coleridge's intellectual duplicity. In 'Confessions', De Quincey's accounts of himself as a scholar of Greek literature, Ricardian economics, and Kantean philosophy are all galvanized by his knowledge that Coleridge too has worked in these areas. As opium addicts, De Quincey's experience of the drug overlaps with Coleridge's in a number of ways, while De Quincey differs from Coleridge – at least on the surface – in his claims about both the moral implications of drugged euphoria and the resolve needed to defeat addiction.